Political theologies in the Hebrew Bible - Brett, Mark G.; Gilmour, Rachelle (Brill | Schöningh, 2023)
In the broadest sense, political theology refers to “God talk” in the context of multiple and often competing perspectives on social life. While political history is firmly established within biblical studies, it is frequently separated from the study of theology and religion. And if political theology has found a place in scholarly conversations within biblical studies, it has often been reduced to specific comparisons with political genres in the ancient world, such as treaty/covenant, or kingship. This volume is an edited collection of 17 essays that seek to broaden the scope of what might count as political theology, throwing new light on older studies and demonstrating the diversity of political theologies in the Hebrew Bible. Each essay demonstrates the integration of political theology with other strands of innovative research in current biblical studies. The essays cover a range of topics such as sovereignty, nation, migration, cultural politics, land holding, and gender.